Simulation of Tool Path Using Conventional Method for Milling Application - Abdullah, Haslina; Shafie, A.M (Research Progress in Mechanical and Manufacturing Engineering, 2020)
Today our manufacturing industry has become more far more advanced compared to decades before. The development and wide application of Computer-Aided Design and Manufacturing (CAD-CAM) software have led to the use of Computer Numerical Controlled (CNC) machines in the manufacturing industry. This software, which includes tool paths, will generate key machining parameters. This study describes the form of tool paths typically used to manufacture a product and how the 3-axis CNC vertical milling machine is used to refine the tool paths. The objective of this study is to simulate the machining time of pocket milling by using a conventional method by using the software CAD/CAM. Second is to investigate the axial and radial depth on machining time. This study can be done by using CAM software which is MasterCAM. The tool paths can be optimized using MasterCAM software through simulations. This program allowed the tool paths to be simulated, and results were obtained in machining time. To achieve the optimal machining time to be used in the actual machining process, parameters such as tool diameter, federate, spindle speed, and cut depth were evaluated. Testing shows that in terms of shortest machining time, there were three styles of machining strategies that were high speed, parallel spiral and Zig-Zag that were more beneficial than any other commodity machining strategies. Based on this study, the tool diameter will achieve the shortest simulation time by using the maximum tool diameter. By referring to the result of this study, three proven results produce the shorter time which is Zig-Zag, High-Speed or Parallel Spiral which is the time for Zig-Zag was 10 hours and 20 minutes and the other two was the closest time with the Zig-Zag. Same goes to cut depth that produced the shortest machining time by the highest cut depth value used by referring to the result of this study, where it can be seen that the difference of 1.5mm could influence the time by 10 seconds above approximately. Lastly, it can be concluded that the machining method and cutting depth are essential factors to achieve a shorter machining time.